Research progress on the relationship between the TOR signaling pathway regulator, epigenetics, and tumor development - Sun, Jiaen; Yang, Minglei; Zhao, Weidi; Wang, Fajiu; Yang, Liangwei; Tan, Chuntao; Hu, Tianjun; Zhu, Huangkai; Zhao, Guofang (Frontiers in Genetics, 2022)
Almost all cellular activities depend on protein folding, signaling complex assembly/disassembly, and epigenetic regulation. One of the most important regulatory mechanisms responsible for controlling these cellular processes is dynamic protein phosphorylation/dephosphorylation. Alterations in phosphorylation networks have major consequences in the form of disorders, including cancer. Many signaling cascades, including the target of rapamycin (TOR) signaling, are important participants in the cell cycle, and dysregulation in their phosphorylation /dephosphorylation status has been linked to malignancies. As a TOR signaling regulator, protein phosphatase 2A (PP2A) is responsible for most of the phosphatase activities inside the cells. On the other hand, TOR signaling pathway regulator (TIPRL) is an essential PP2A inhibitory protein. Many other physiological roles have also been suggested for TIPRL, such as modulation of TOR pathways, apoptosis, and cell proliferation. It is also reported that TIPRL was increased in various carcinomas, including non-small-cell lung carcinoma (NSCLC) and hepatocellular carcinomas (HCCs). Considering the function of PP2A as a tumor suppressor and also the effect of the TIPRL/PP2A axis on apoptosis and proliferation of cancer cells, this review aims to provide a complete view of the role of TIPRL in cancer development in addition to describing TIPRL/PP2A axis and its epigenetic regulation.